THEORETICAL BASIS FOR LANGUAGE MANAGEMENT (PROGRAMS FOR CORPORATE TRAINING IN SCIENTIFIC RESEARCH LINGUISTIC CENTRE OF MESI’S TVER BRANCH - NILC) - Logutenkova, Tatyana; Sokolova, Alina (European Scientific Journal, ESJ, 2014)
Scientific Research Linguistic Centre (NILC) is a department of Moscow State University of Economics, Statistics and Informatics (MESI), Tver Branch. Being established as a multifunctional linguistic centre NILC focuses on providing various services from teaching languages and developing educational programs to translation. NILC’s practical activity is based on scientific research in the field of effective methods of teaching, learning tools, forms and models. Despite a number of different interpretations of language management, from the choice of language for a certain communication be a bilingual or multilingual NILC has offered a new understanding of this term which is schematically represented as Linguistic school an employee of a linguistic school an employee of an enterprise  activity of an enterprise NICL implements its language management on the theoretical basis of its previous research – anthropocentric hierarchical model of teaching a foreign language, visualization of lingual signs, prospective interactivity and various modes of tutor’s support. An important stage in corporate education is developing profiles of competence in a foreign language for various groups of employees. The profile is constructed in compliance with the requirements for the knowledge of a foreign language which are necessary to meet for certain positions in an enterprise or company. Academic plans and learning content of the courses of foreign languages are carried out accordingly. The keys elements for effective language management are meeting the requirements for the positions within the company which is achieved through extensive preparation work and flexibility in carrying out programs for corporate education.